FRACTIONAL APPROACH FOR DIRAC OPERATOR INVOLVING M-TRUNCATED DERIVATIVE - Ercan, Ahu (Ankara Univ, Fac Sci, 2024)
In this study, we examine the basic spectral information for systems governed by the Dirac equation with distinct boundary conditions, utilizing a modified form of local derivatives known as M -truncated derivative (MTD). The spectral information discussed includes the representation of solutions in the form of integral equations, the asymptotics vector -valued eigenfunctions and eigenvalues, and their normalized forms, all within the context of the MTD method that incorporates truncated Mittag-Leffler functions. This type of MTD provides the features of integer -order operator theory. Also, by virtue of the parameters alpha and gamma , we analyze and compare the solutions with graphs in terms of different potentials, different eigenvalues and different orders. Thus, the aim of this article is to consider spectral structure of Dirac system in frame of M -truncated derivative by proping with visual analysis.
Keywords: . M-truncated derivative; Dirac operator; spectral data; visual results